Which is the Correct Discount Rate? Arithmetic Versus Geometric Mean - Martin Kipp; Christian Koziol (Credit and Capital Markets – Kredit und Kapital, 2020)
The paper revisits the two major concepts for average historical returns, i.?e., the arithmetic mean and the geometric mean, in order to clarify which approach must be used for which application. Conducting a rigorous derivation with a geometric Brownian motion, we can explain that the appropriate discount rate refers to the mean discrete return and, therefore, to the arithmetic mean rather than the often wrongly applied geometric mean. Likewise, the prominent CAPM relationship between the expected asset return and the expected market return is only valid for the arithmetic mean rather than the geometric mean. Using historical data for the German stock index, we illustrate that an inconsistent application can cause severe deviations from the meaningful ex-ante expected performance of an asset, the true discount rate, the true CAPM risk-adjusted return, and the intended performance scenarios of packaged retail and insurance-based investment products (PRIIPs) within the key information documents (KIDs).
Keywords: G12; 330; Asset returns; Arithmetic mean; Geometric mean; Geometric Brownian Motion; Discount rate; CAPM; PRIIPs